CHARACTERIZATION IN THE NOVEL ENTITLED SONS AND LOVERS BY DH LAWRENCE - La Muhiddin (Center of Language and Cultural Studies, 2015)
This study is qualitative designed to analyze the character of the novel through psychological approach. The subject of the study is the works of D.H. Lawrence, focusing on the novel